Methods to Evaluate the Potential Clinical Significance of Antibodies to Red Blood Cells. Issue 8 (4th August 2022) - Boligan, Kayluz Frias; Sandhu, Gurleen; Branch, Donald R.
Abstract: Immune‐mediated red blood cell (RBC) destruction due to antibodies is an ongoing problem in transfusion medicine for the selection of the safest blood. Serological testing often revealed incompatibility with donors' RBCs. When this incompatible blood was transfused, destruction was due mostly to extravascular‐mediated phagocytosis of the antibody‐opsonized RBCs; however, intravascular hemolysis was sometimes observed without explanation. Based on serology, antibodies with potential for clinical sequalae could not be ascertained; thus, antigen‐negative blood was usually selected for transfusion to avoid problems. Antibodies to antigens having very high frequency in the general population (>95%), however, made selection of antigen‐negative blood difficult and sometimes impossible. Some patients, who were sensitized by previous transfusions or by pregnancy, developed multiple antibodies, again creating a problem for finding compatible blood for transfusion, without the ability to discern which of the antibodies may be clinically irrelevant and ignored. Transfusion medicine scientists began searching for an in vitro means to determine the in vivo outcome of transfusion of blood that was serologically incompatible. Methods such as chemiluminescence, monocyte‐macrophage phagocytosis, and antibody‐dependent cellular cytotoxicity (ADCC) were described. Over the years, the monocyte monolayer assay (MMA) has emerged as the most reliable in vitro assay for the prediction of the clinical relevance of a given antibody. ADCC has not been fully studied but has the potential to be useful for predicting which antibodies may result in intravascular hemolysis. This article captures the protocols for the implementation and readout of the MMA and ADCC assays for use in predicting the clinical significance of antibodies in a transfusion setting. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Monocyte monolayer assay (MMA) Basic Protocol 2 : Antibody‐dependent cellular cytotoxicity assay (ADCC)